PENGETAHUAN PERAWAT TERHADAP PELAKSANAAN TIMBANG TERIMA PASIEN SESUAI SOP - Febrina, Wiwit; yenni, Yenni (REAL in Nursing Journal, 2018)
Nursing is one of a profession front for health workers in this effort to ensure the quality of health center in the community. Handover is good quality health services to offer a service nursing on a patient care, To optimize the role and function of nurse especially function to independence nurse. This research aims to know the the relations knowledge of a nurse with patient handover implementation as procedure. The kind of research used is descriptive analytic with the approach cross sectional. A population that used is nurse who were 101 people from 101 a person who uses technique total of sampling. The analysis in use is analysis univariat and bivariat. The results of the study was obtained 42,6 % nurse possess wisdom that low and 31.7 % nurse of these stations have the implementation of patient a less well , testing shows statistic been gained there are the kind of relationship is meaningless between knowledge a nurse with the implementation of these stations received patients ( p = 0,094 ). Based on the research done can be concluded that there was a correlation meaningful of the incentives a nurse with the implementation of the weigh received patients appropriate with the sop .Was recommended to researchers , the hospital to continue to motivate nurse in the implementation of the weigh received patients appropriate with the procedure.  Keywords: Knowledge, The Implementation of handover